The final strife : a novel - El-Arifi, Saara (El-Arifi, Saara. Ending fire trilogy, 2022)
"Sylah dreams of days growing up in the resistance, being told she would spark a revolution that would free the Empire from the red-blooded ruling classes' tyranny. That spark was extinguished the day she watched her family murdered before her eyes. Anoor has been told she's nothing, no one, a disappointment by the only person who matters: her mother, the most powerful ruler in the Empire. But dust always rises in a storm. Hassa moves through the world unseen by upper classes, so she knows what it means to be invisible. But invisibility has its uses: It can hide the most dangerous of secrets, secrets that can reignite a revolution. As the Empire begins a set of trials of combat and skill designed to find its new leaders, the stage is set for blood to flow, power to shift, and cities to burn"--